2023
DOI: 10.3389/fmolb.2023.1161111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a peptide ligand for human ALDH3A1 through peptide phage display: Prediction and characterization of protein interaction sites and inhibition of ALDH3A1 enzymatic activity

Abstract: Aldehyde dehydrogenase 3A1 (ALDH3A1) by oxidizing medium chain aldehydes to their corresponding carboxylic acids, is involved in the detoxification of toxic byproducts and is considered to play an important role in antioxidant cellular defense. ALDH3A1 has been implicated in various other functions such as cell proliferation, cell cycle regulation, and DNA damage response. Recently, it has been identified as a putative biomarker of prostate, gastric, and lung cancer stem cell phenotype. Although ALDH3A1 has mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In HO, the most coupled genes are Aldh3a1 and Gapdh , with only 10 (25.5%) synergistic partners, while the uncoupled genes (no partners) are Acss2 , Acyp2 , Eno4 , Gapdhs , and Pfkl. Aldh3a1 is a putative biomarker of lung cancer [ 70 ], while Gapdh was reported as critical for stem cell therapy of pulmonary hypertensive females [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In HO, the most coupled genes are Aldh3a1 and Gapdh , with only 10 (25.5%) synergistic partners, while the uncoupled genes (no partners) are Acss2 , Acyp2 , Eno4 , Gapdhs , and Pfkl. Aldh3a1 is a putative biomarker of lung cancer [ 70 ], while Gapdh was reported as critical for stem cell therapy of pulmonary hypertensive females [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In HO, the most coupled genes are: Aldh3a1 and Gapdh with only 10 (25.5%) synergistic partners, while the uncoupled genes (no partners) are: Acss2, Acyp2, Eno4, Gapdhs, Pfkl. Aldh3a1 is a putative biomarker of lung cancer [57], while Gapdh was reported as critical for stem cell therapy of pulmonary hypertensive females [58].…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic studies showed that the peptide exhibits a significant inhibitory effect against ALDH3A1's activity which is comparable to CB29 inhibition. Furthermore, bioinformatic analysis identified an area close to the substrate binding site as the most probable peptide binding site on the protein [249].…”
Section: Aldh2 Specific Inhibitorsmentioning
confidence: 99%